Literary dimension «Tarihi Rashidi» (Journal of Oriental Studies, 2019)
Although the linear works of heritage remained of the Middle Ages of Persian have been written in relation to a particular subject; but other aspects of them, such as literature, folklore, language, history, sociology, etc., are noteworthy. A review of these aspects will help us to better understand the Middle Ages of Persian and the linear works of this era. In this article, we will review “Rashidi’s History” of Mirza Mohammad Heydar Daghlat, who has been compiled in the history of the Mongols in the fourteenth to fifteenth centuries between -1542. e will show that Mirza Haydar grew up in what literary en-1542. e will show that Mirza Haydar grew up in what literary ene will show that Mirza Haydar grew up in what literary ene will show that Mirza Haydar grew up in what literary enill show that Mirza Haydar grew up in what literary environment and how was his Literary taste? e will refer to the level of literary knowledge of the author. e will also discuss how to use literary esthetic in the historical text. In the meantime, we will look at the mystical, psychological, and personal character of the work, and examine the type of literary skill used. Key words: Rashidi’s history, Mirza Haydar, literary dimension, literary skill, likeness.